Analisis Ketertarikan Wakaf Generasi Muda dengan Teknologi Acceptance Model - Putri Ramadhanty Ningtias; Prameswara Samofa Nadya (Perbanas Institute, 2022)
Based on CAF World Giving Index 2021, Indonesia is the most generous country in the world, with the highest donor index. Supported by a high number of Moslems, there is a high potential for growth of Islamic philanthropy. Waqf as a form of Islamic philanthropy is currently still underdeveloped. One of the contributing factors is the lack of socialization. The purpose of this study was to analyze the interests of generations Y and Z both as a donator of berkahwakaf.id site with a technology acceptance model (TAM) approach. This research design uses associative research with a quantitative approach using data of 100 respondents as sample, analyzed with PLS method. The results showed that perceived benefits had a significant positive effect on interest, while user convenience had a significant negative effect on interest. Attitude has a significant positive effect on interest, usefulness has a positive effect on attitudes, while user convenience has a significant negative effect.